Bilateral Flows of Foreign Direct Investment between China and European Union - Klimek, Artur (Wzajemne przepływy bezpośrednich inwestycji zagranicznych między Chinami i Unią Europejską, 2010)
The attention of the author was focused on capital flows in the form of foreign direct investment (FDI) between China and European Union countries. The author analysed the volume of bilateral flows of foreign direct investment and searched for the answer about its determinants. The main aim of the paper was an analysis of Chinese outward foreign direct investment as a new, but gaining significance, phenomenon. Important part of the paper was a recommendation of future development of FDI flows between the countries.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 257-265
Keywords: foreign derect investment; China; European Union